Text as Locus, Inscription as Identity: On Barbara Honigmann's Roman von einem Kinde - Marilyn Sibley Fries (Studies in 20th & 21st Century Literature, 1990)
Barbara Honigmann's Roman von einem Kinde (1986) constitutes the author's attempt at narrative self-definition. In this and other regards, it is similar to Christa Wolf's Kindheitsmuster (1976; Patterns of Childhood, 1980), with which it is briefly compared. Honigmann's slim collection of stories, conceived by her as "sketches for self-portraits and landscapes," depicts the absolute isolation ofthe female Jewish narrator in the GDR and her search for community (Heimat) via language. Simultaneously, it records that narrator's desire to identify "places of transition," "boundaries at which conditions change" without fixing these in a static prison of text. The narrator-mother merges with the child born in the first story as, in the following ones, she comprehends the insignificance of her social (con)text, finally to simulate her own birth and the envied preverbal infant stage by means of self-expulsion—from the GDR via a "threefold salto mortale into the "Judaism of the Thora" in Strasbourg—into a "foreign language among foreign people." The narrator/author's position at a transitional boundary, underscored by the self-portrait that adorns the book's dust jacket, acknowledges the territory between two illegible texts and her reluctance to sacrifice "true reality" (wahre Wirklichkeit) by transforming "human being" into "text" (Mensch into Schrift)—a reluctance engendered by her meeting with Gershom Scholem in the central story of the volume.
Keywords: Barbara Honigmann; Roman von einem Kinde; narrative self-definition; self-definition; Christa Wolf; Kindheitsmuster; Patterns of Childhood; Honigmann; sketches; self-portraits; landscapes; isolation; female Jewish narrator; GDR; Heimat; community; language; narrator; places of transition; boundaries; change; text; narrator-mother; mother; child; born; social; context; birth; infant; stage; self-expulsion; DDR; Judaism of the Thora; Strasbourg; foreign language; foreign; author; self-portrait; true reality; wahre Wirklichkeit; human being; Mensch; Schrift; Gershom Scholem